2022
DOI: 10.1148/radiol.212536
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Unnecessary Biopsy after Multiparametric Prostate MRI with VERDICT Analysis: The INNOVATE Study

Abstract: GENITOURINARY IMAGINGM ultiparametric MRI (mpMRI) is now established as the first-line investigation for suspected prostate cancer (PCa) (1), but overall specificity for clinically significant cancer (csPCa) (Gleason score 314) is reported at a modest 37% (2,3). This results in one in two men with positive mpMRI findings undergoing biopsy, the results of which were negative for significant cancer, with associated morbidity and a health economic cost (4-6).Adjunct markers have been proposed to complement mpMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Furthermore, T2-weighted signal in the BP indicated the presence of csPCa with surprising accuracy. Indeed, the csPCa discrimination performance achieved using T2-weighted signal in the BP alone was comparable to the performance reported for methods that examine signal properties within radiographically identified lesions (20)(21)(22).…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, T2-weighted signal in the BP indicated the presence of csPCa with surprising accuracy. Indeed, the csPCa discrimination performance achieved using T2-weighted signal in the BP alone was comparable to the performance reported for methods that examine signal properties within radiographically identified lesions (20)(21)(22).…”
Section: Discussionsupporting
confidence: 53%
“…The improved performance of rVERDICT over VERDICT is probably due to the compensated relaxationinduced biases on the signal fractions and the extra information on the relaxation times. Additional numerical simulations we performed showed that rVERDICT reduces the error of classic VERDICT on (f ic , f ees , f vasc ) by respectively (65, 93, 12) percentage points for the ex vivo and (64,83,20) percentage points for the in vivo case (see Supplementary Material and Supplementary Fig. S4).…”
Section: Discussionmentioning
confidence: 90%
“…Results from the recent clinical trial INNOVATE 19 reveal that VERDICT f ic can discriminate between Gleason 3 + 3 and 3 + 4 lesions (AUC = 0.93, p = 0.002) 16 and that its diagnostic performance in identifying lesions with clinically significant PCa (AUC = 0.96) is higher than that of ADC from mp-MRI (AUC = 0.85, p < 0.001) and prostate-specific antigen density (AUC = 0.74, p < 0.001) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, RSIrs outperformed both sDWI and aDWI in the present study. Other promising multi-compartment models have proved to be superior to conventional multiparametric MRI, like a biomarker derived from VERDICT that outperformed ADC in the detection of csPCa 14 . Hybrid multidimensional MRI acquisitions also showed promising results for classifying csPCa with a reported AUC of 0.94 34 .…”
Section: Discussionmentioning
confidence: 99%
“…More advanced DWI models have been developed to better account for tissue microstructure, including intravoxel incoherent motion imaging 8,9 , diffusion kurtosis imaging 10,11 , Vascular, Extracellular, and Restricted Diffusion for Cytometry in Tumor (VERDICT) [12][13][14] , hybrid multidimensional MRI (HM-MRI) [15][16][17][18] , and Restriction Spectrum imaging (RSI) 12,19 . In RSI, the diffusion signal is modeled as a weighted sum of different compartments representing different tissue types 19,20 .…”
Section: Introductionmentioning
confidence: 99%